Recent progress of triboelectric nanogenerators: From fundamental theory to practical applications - Luo, Jianjun; Wang, Zhong Lin (EcoMat (Beijing, China), 2020)
For the development of the internet of things (IoTs), big data, and artificial intelligence, widely distributed sensing network is the most essential element, which has to be driven by the energy storage unit, with a limited lifetime and environmental concerns. Given that the wide distribution and high mobility of these numerous sensors, the success of the IoTs and sustainable development of human society call for renewable distributed energy sources. Since triboelectrification effect is ubiquitous and universal in our living environment, the triboelectric nanogenerator (TENG) for mechanical energy harvesting and self‐powered sensing developed by Wang and co‐workers is one of the best choices for this energy for the new era. In this review, the recent progress of TENGs from fundamental theory to practical applications is systematically summarized. First, the mechanism of contact electrification, first principle theory, working principle, working modes, and figure of merits of the TENG are introduced. Furthermore, recent important progress in four major TENG applications, including micro/nano power sources, active self‐powered sensors, large‐scale blue energy, and direct high‐voltage power sources are reviewed. In the end, some perspectives and challenges for the future development of TENG are also discussed. The recent progress on the development of triboelectric nanogenerators (TENGs) is systematically reviewed. The basic knowledge and fundamental theory of TENGs are first introduced. Subsequently, recent important progress in four major application fields of TENGs are also summarized. At last, current challenges and future outlooks regarding to the TENG field are also discussed.